The implementation of zakat in eradicate poverty: case study in Selangor / Anis Syazana Azeman - Azeman, Anis Syazana (Academy of Contemporary Islamic Studies (ACIS), 2016)
Zakat is an obligatory practice which must be implemented under the supervision from responsible and authorized bodies and institution. Zakat has been told to us by the Prophet Muhammad S.A.W that it is very important thing to be manage properly. One of the effect of zakat is it could eradicate the poverty problem among the community. And today, the issue about distribution of zakat in eradicating the poverty often been said by many people. The community starts questioning why does the problem of poverty still exist although the total amount of zakat collected keep increasing from years to years. How is the management of collecting and distributing of zakat fund was run? Thus, this study is done with the intend of reviewing how is the concept of zakat and its implementation in eradicate the poverty problem.